A short course in geology for civil engineers - Matthews, M. C. (Thomas Telford, 2007)
This book explains the processes of how the ground is formed and therefore what it is made of and how it behaves as an engineering material. This enables the civil engineer to work from a few first principles to decide if the ground is an asset or a hazard.